Clinical case: paroxysmal tachycardia attack in a newborn with multiple heart rhabdomyomas - Chernenkov Yu.V. (Саратовский научно-медицинский журнал, 2016)
The purpose of the clinical observation is to study the early symptoms of multiple heart rhabdomiomas of a newborn; to draw the attention of specialists on one of the rarely occurred problems in the neonatal practice.